#TITLE_ALTERNATIVE# - NUR ARIBAWONO (NIM 13202007), ALFA
Internet's growth has been rising rapidly over the decade. Many websites are gaining more popularity than ever before. For these kinds of websites, their content must be delivered all over the Internet quickly at any given time. Some part of the documents may be requested by the same users repeatedly, and popular documents can be accessed by users from different time zones all day. This can lead to server load and bandwidth inefficiency. Caching proxy is designed to increase web access performance by keeping recently accessed documents in a local buffer, and thereby reduce user's access time while saving the precious bandwidth. Although hierarchical caching proxy has became a popular strategy to increase the performance of standalone caching proxy, there is still no standard procedure to determine the best hierarchy configuration given a set of machines and the workload they have to serve. This final assignment presets a method of implementing caching proxy hierarchies in campus environment along with the policy implemented for the clients using the cache. This implementation allows us to easily observe configurations used, and opens the possibility of tuning the cache hierarchies. The cache is implemented using Squid open-source software. The performance of the server machines measured using CIS Scoring Tools shows a final rating of 5 or near 5, which means an intermediate level of security. The design of the hierarchy also achieves 20,68% hit rate, which means that every Mbps of the traffic served by the proxy, approximately one fifth of them is served from the local cache and thereby saving the bandwidth for other use. Utilizing user bandwidth management, including the connection limit policy, users can still manage to obtain up to 38,71 kbps per-connection or 271 kbps per-user average bandwidth. Altogether, users will have a responsive web access with efficient bandwidth usage.